Kajian Ekonomi Model Pengelolaan Sumberdaya Perikanan Cakalangdi Pantai Utara Aceh - Naufal, Agus; Kusumastanto, Tridoyo; Fahrudin, Achmad (Jurnal Aplikasi Manajemen, 2016)
Abstract: Overfishing has made marine resources will be exhausted in the future, consequently this resource must be managed properly. Good fisheries management should consider many aspects. Therefore, this study aims to identify the policy and the relationship between the sub-systems of ecological, economic, and social aspects, as well as to calculate the financial feasibility of Skipjack fishery on the north beach of Aceh. The method used in this study were dynamic analysis, and feasibility analysis. The results showed in the long term based on the total allowable effort policy simulation and additional effort restrictions, the optimal management policy that gives the biggest economic rent is Rp. 40.329 billion will be achieved in 2033 with a total production of 3,191 tons per year. Skipjack fishing sector is still able to absorb workers without excessive depletion with the enforcement policy of limiting the addition of effort. Dynamic analysis showed that optimal and sustainable Skipjack resource management should be limited at the level of maximum economic rent then an increase of 20 percent effort per year can be added until the level of sustainable effort. NPV is Rp. 2.311 billion and the value of Net Benefit-Cost Ratio (Net B/C) is 1.97, indicating that investment of Skipjack purse seine vessels 40 GT on the North Beach of Aceh is feasible.